(untitled) (Research, Society and Development, 2021)
Objective: To verify the rate of systemic changes observed in individuals seen at the Oral and Maxillofacial Surgery and Traumatology clinics of the Undergraduate Dentistry course at the Faculty of Dentistry of Bauru (FOB-USP). Methodology: a retrospective study of the medical records of individuals seen at the Oral and Maxillofacial Surgery and Traumatology clinics of the third and fourth years of the Dentistry course at FOB-USP, from January 1, 2015, to June 30, 2017. Data collection was performed based on information from the anamnesis obtained during the initial care of the patients and recorded in the medical records. The selected data were name, age, address, diagnosed systemic disease, current and/or past medical treatments, proposed surgical treatment, and, if there was, patient return after medical treatment for surgery. The medical records of individuals under the age of 18, patients who did not have any systemic changes, or those with systemic changes observed outside the initial care period were excluded. RESULTS: The sample consisted of 266 medical records and 119 of these were from individuals who had systemic changes (44.7%), with systemic arterial hypertension being the most common (33.1%), followed by diabetes mellitus (17.8%). Conclusion: the high prevalence of individuals with systemic alterations and who require dental surgical intervention was proven, which implies the need for a correct anamnesis and preoperative evaluation so that these cases are managed to avoid trans and/or post-operative, systemic, and/or local.